THE EFFECT OF ISLAMIC SOCIAL REPORTING MODERATION AND ISLAMICITY PERFORMANCE INDEX ON THE MILLENNIAL GENERATION THIRD-PARTYFUNDS - Laila Nursaputri; Hendra Harmain (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the moderating effect of Islamic social reporting, Islamicity performance index on millennial generation on third party funds through Islamic social reporting as a moderating variable. This study uses quantitative methods. This study uses purposive sampling in taking samples from a population of 18 millennial generations. Data analysis uses multiple linear regression and moderate regression analysis (MRA). The results show that ISR has a significant effect on the Islamic Performance index in millennial generation banking. The Islamic Performance index does not have a significant effect on the millennial generation on third party funds. Likewise, the millennial generation does not have an effect on third party funds in Islamic banking. ISR has a significant effect on the Islamic Performance index in the millennial generation. ISR is only able to moderate the effect on financial performance in the millennial generation. However, the Islamic Performance index is not able to influence the millennial generation on third party funds. ISR, IPI has a coefficient value of -0.160, a t-value of -2.246 and a sig. value. 0.039 < 0.05, meaning that ISR can moderate the influence of IPI on the millennial generation (H5 is accepted). Ipi and the millennial generation have a coefficient value of -0.003, a t-count value of -0.250 and a sig. value of 0.806 > 0.05, meaning that Ipi and the millennial generation cannot moderate the influence on third parties (H6 is rejected). Ipi's Isr has a coefficient value of -0.064, a t-count value of -0.728 and a sig. value of 0.477 > 0.05, meaning that ISR cannot moderate the influence of IPI on the millennial generation (H7 is rejected).